Harry Wild. Series 2 [videorecording (DVD)] - Logan, David, 1969- (Acorn, 2024)
Harry and her young partner in PI work, Fergus, take on cases from missing persons to murders, but when Fergus's mother turns up, years after abandoning him, they have a deeply personal mystery to solve: Can he trust her?